CUTANEOUS LARVA MIGRANS – A CASE REPORT - Macias, Vasco Coelho; Carvalho, Rodrigo; Chaveiro, Alexandra; Cardoso, Jorge (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Cutaneous larva migrans is one of the most frequent dermatoses among travelers returning from the tro- pics. Ancylostoma braziliense, a larva that resides in the intestines of infected dogs and cats, is the most frequent agent of the disease. Humans are affected when they contact with contaminated soil. We present the case of a Portuguese 39-year-old teacher that after returning from vacation in northeastern Brazil, deve- loped a skin eruption localized to the 4th interdigital fold and adjacent portion of the dorsum of the feet, consisting of multiple erythematous, pruritic and serpiginous cutaneous trails, suggestive of cutaneous larva migrans. Complete cure was achieved after Albendazole therapy. Due to the increased frequency of migration flows, tropical dermatoses may become more common in temperate coun- tries. We emphasize the importance of tourists counseling and the use of protective footwear to prevent this disease. KEYWORDS – Larva migrans; Ancylostoma; Skin.